A strategy for the highly efficient production of docosahexaenoic acid by Aurantiochytrium limacinum SR21 using glucose and glycerol as the mixed carbon sources. (February 2015) - Li, Jing; Liu, Ruijie; Chang, Guifang; Li, Xiangyu; Chang, Ming; Liu, Yuanfa; Jin, Qingzhe; Wang, Xingguo
Highlights: Glucose facilitated rapid growth and lipid synthesis as sole carbon source. Glycerol promoted DHA accumulation but gave low productivity. Fed-batch culture was performed using glucose and glycerol as mixed carbon sources. The strategy of mixed carbon sources efficiently improved DHA yield and productivity. Abstract: Glucose and glycerol are useful carbon sources for the cultivation of Aurantiochytrium limacinum SR21. Glucose facilitates rapid growth and lipid synthesis, and glycerol promotes the accumulation of docosahexaenoic acid (DHA) in A. limacinum SR21. To improve the DHA productivity of A. limacinum SR21, shake flask and fed-batch cultures were performed using glucose and glycerol as mixed carbon sources (MCSs). Along with optimization of the MCSs, the best DHA yield and productivity (32.36 g/L and 337.1 mg/L/h) were obtained via fed-batch fermentation with maintenance of a constant air supply. The DHA productivity was 15.24% higher than that obtained using glucose as single carbon source (SCS). This study presents a highly efficient and economic strategy for the production of DHA by A. limacinum SR21.